Bark harvesting by human population shapes tree allometry in an economically important species of the Brazilian savanna - Baldauf, Cristina; Dias, Arildo S.; Corrêa, Christiane E.; Santos, Flavio A.M. (Forest ecology and management, 2021)
[Display omitted] •Non-timber forest products harvesting can change tree allometry.•Height-stem diameter relationships in H. drasticus are affected by bark harvesting.•High levels of debarking slow down H. drasticus height growth.•The limit of 50% of debarking avoids negative effects on H. drasticus height growth. Theoretical models of allometric scaling provide an important framework for understanding and predicting how and why the morphology and function of organisms vary with scale. However, the predictions of ‘universal’ scaling models for vascular plants do not consider different environments and disturbance types which can reduce the predictive power of these models. One important source of disturbance in tropical regions is the harvesting of non-timber forest products, such as leaves, flowers, resins and barks. In this context, we examine the influence of bark harvesting and different light environments on scaling of the height and diameter of Himatanthus drasticus (Apocynaceae), an economically important tree species harvested by several local communities living in the Brazilian savanna. By considering this species as a model system and using Bayesian regression, we show that bark harvesting modifies tree allometry and that the empirical scaling exponents diverge from the theoretical predictions. In addition, the results of a mechanistic model of tree growth revealed that bark harvesting affects tree height and that this effect varies independently of the light environment. On the other hand, trees with higher bark harvesting levels presented lower height growth rates when compared to trees without bark harvesting or those with<50% of bark harvesting. Our results highlight the importance of including bark harvesting as a source of disturbance that can cause differences between the observed scaling relationships and those predicted by theoretical models. Finally, from the management perspective, we observed that high levels of bark harvesting could compromise the plant height growth of the debarked trees. Therefore, our recommendation for the management of this species is that the previously defined limits of 50% of bark harvesting should be maintained to avoid the negative effects of harvesting on the tree height over time.